Parkour Fails and Hébertisme: laughing at the New Man - Smith, M (Taylor & Francis, 2023)
“Parkour Fails” represent a genre of comedic YouTube videos consisting primarily of compilations of failed stunts by practitioners of the extreme sport of parkour. Parkour originated in the suburbs of Paris and involves creative reappropriation of urban furniture. In mass media, it is usually coded as a defiant challenge to urban norms and a symbol of multicultural France’s growing social mobility. However, it was inspired by Hébertisme, a training system embraced by eugenicists and the Vichy government as a way to cultivate the New Man, an idealized figure incarnating fascist values. While parkour athletes do not endorse fascism, many promote their practice with a rhetoric of decadence and decline, return to nature, and masculine power that echoes Vichy’s New Man ideology. This article explores the extent to which parkour fail videos humorously problematize that rhetoric.